2016
DOI: 10.1111/jgh.13060
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the gluten‐free diet can achieve the therapeutic goals in almost all patients with coeliac disease: A 5‐year longitudinal study from diagnosis

Abstract: Dietary compliance is associated with a high chance of healing the intestinal lesion and correction of specific body compositional abnormalities. The time course differed with body fat improving within 1 year, and correction of the mucosal lesion and improvement in lean mass and bone mass taking longer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
(42 reference statements)
2
51
1
3
Order By: Relevance
“…In a study of 52 patients who abided by a strict GFD, Newnham et al have reported that it took 5 years for 89% of the subjects to achieve mucosal response [10]. GFD has been shown to result in significant improvement in BMD, although the magnitude of the change shown in studies is far less than was achieved with the combination treatment of GFD and alendronate in our patient.…”
Section: Discussioncontrasting
confidence: 41%
“…In a study of 52 patients who abided by a strict GFD, Newnham et al have reported that it took 5 years for 89% of the subjects to achieve mucosal response [10]. GFD has been shown to result in significant improvement in BMD, although the magnitude of the change shown in studies is far less than was achieved with the combination treatment of GFD and alendronate in our patient.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, other causes of villous atrophy should have been excluded and the initial diagnosis of CD should be confirmed. Complete mucosal recovery can take up to 5 years on a GFD (7). RCD is often classified into types 1 and 2 based on immuno-phenotypic aberrancies of intraepithelial lymphocytes (IELs).…”
Section: Defintions Of Refractory Celiac Diseasementioning
confidence: 99%
“…Es interesante que un 24,1% de los pacientes (7 niños), a pesar de pensar que están haciendo mal el régimen, ya sea porque comen gluten en forma evidente o porque no tienen clara las indicaciones de alimentación, mantienen ambas serologías negativas. Esto apoya la idea que la serología no es un buen indicador para hacer el seguimiento (11,(27)(28)(29) ; abre también la posibilidad que algunos pacientes tengan cierta tolerancia a cantidades pequeñas de gluten sin que se despierte en ellos la respuesta autoinmune detectable (30) . Otra posibilidad es que el tiempo transcurrido entre la trasgresión de la dieta y la medición de marcadores haya sido insuficiente para producir el cambio detectable.…”
Section: Discussionunclassified